Prediction of High-Grade Vesicoureteral Reflux after Pediatric Urinary Tract Infection: External Validation Study of Procalcitonin-Based Decision Rule - Leroy, Sandrine; Bouissou, Francois; Fernandez-Lopez, Anna; Gurgoze, Metin K.; Karavanaki, Kyriaki; Ulinski, Tim; Chalumeau, Martin (Public Library Science, 2011)
Background: Predicting vesico-ureteral reflux (VUR) >= 3 at the time of the first urinary tract infection (UTI) would make it possible to restrict cystography to high-risk children. We previously derived the following clinical decision rule for that purpose: cystography should be performed in cases with ureteral dilation and a serum procalcitonin level >= 0.17 ng/mL, or without ureteral dilatation when the serum procalcitonin level >= 0.63 ng/mL. The rule yielded a 86% sensitivity with a 46% specificity. We aimed to test its reproducibility. Study Design: A secondary analysis of prospective series of children with a first UTI. The rule was applied, and predictive ability was calculated. Results: The study included 413 patients (157 boys, VUR >= 3 in 11%) from eight centers in five countries. The rule offered a 46% specificity (95% CI, 41-52), not different from the one in the derivation study. However, the sensitivity significantly decreased to 64% (95% CI, 50-76), leading to a difference of 20% (95% CI, 17-36). In all, 16 (34%) patients among the 47 with VUR >= 3 were misdiagnosed by the rule. This lack of reproducibility might result primarily from a difference between derivation and validation populations regarding inflammatory parameters (CRP, PCT); the validation set samples may have been collected earlier than for the derivation one. Conclusions: The rule built to predict VUR >= 3 had a stable specificity (ie. 46%), but a decreased sensitivity (ie. 64%) because of the time variability of PCT measurement. Some refinement may be warranted.
Keywords: Acute Pyelonephritis; Antibiotic-Prophylaxis; Bacterial-Infections; Febrile Infants; Children; Diagnosis; Emergency; Multicenter; Markers